2017
DOI: 10.1159/000473703
|View full text |Cite
|
Sign up to set email alerts
|

Combining Cystatin C and Creatinine Yields a Reliable Glomerular Filtration Rate Estimation in Older Adults in Contrast to β-Trace Protein and β2-Microglobulin

Abstract: Background: The glomerular filtration rate (GFR) is the most important measure of kidney function and chronic kidney disease (CKD). This study aims to validate commonly used equations for estimated GFR (eGFR) based on creatinine (cr), cystatin C (cys), β-trace protein (BTP), and β2-microglobulin (B2M) in older adults. Method: We conducted a validation study with 126 participants aged between 72 and 98 with a mean measured GFR (mGFR) by iohexol clearance of 54 mL/min/1.73 m2. The eGFR equations (CKD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 38 publications
2
36
1
1
Order By: Relevance
“…Differences between creatinine‐ and cystatin C‐based equations are similar to those observed by Jacobs et al in frail elderly psychiatric patients. However, these differences were notably larger in our population compared with similar studies in community‐dwelling older populations . CKD‐EPI Cr is commonly used for medication prescribing in clinical settings, while CG Cr is often used for pharmacokinetic studies during drug development and for medication prescribing .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Differences between creatinine‐ and cystatin C‐based equations are similar to those observed by Jacobs et al in frail elderly psychiatric patients. However, these differences were notably larger in our population compared with similar studies in community‐dwelling older populations . CKD‐EPI Cr is commonly used for medication prescribing in clinical settings, while CG Cr is often used for pharmacokinetic studies during drug development and for medication prescribing .…”
Section: Discussioncontrasting
confidence: 70%
“…In 2011, the CKD‐EPI equation was adapted for cystatin C (CKD‐EPI Cys ), and this equation is thought to be more accurate in patients with low body mass index . However, a 2012 version of CKD‐EPI combining both creatinine and cystatin C (CKD‐EPI Comb ) is regarded by many as the most accurate estimator of kidney function in community‐dwelling older populations . Two more eGFR equations were developed specifically for older patients by the Berlin Initiative Study (BIS) based on creatinine (BIS Cr ) or a combination of creatinine and cystatin C (BIS Comb ), and it has recently been suggested that these equations are the most accurate in elderly populations .…”
Section: Introductionmentioning
confidence: 99%
“…While lacking detailed medical histories, we can only speculate on whether a concurrent illness such as acute kidney injury or hemodynamic change caused a transient increase in the eGFR. However, the cross-sectional point prevalence of CKD cysC appears to be higher in the OPRA cohort than other studies, possibly due to the heterogeneity of other populations, especially regarding age span, analytical methods, and study equations [16,[24][25][26]. Environmental and lifestyle factors may also affect CKD prevalence between countries [27].…”
Section: Discussionmentioning
confidence: 81%
“…To counterbalance this, we also chose CAPA cysC [22], which did include elderly subjects in its development. Likely, it performs better than CKD-EPI cysC in this age-group [24,25]. Furthermore, another equation using cysC is Full Age Spectrum equation (FAS), showing comparable performance as CAPA [30].…”
Section: Discussionmentioning
confidence: 85%
“…As a marker of glomerular filtration, serum BTP may have an advantage over serum cystatin C in patients treated with glucocorticoids, including those after renal transplantation [1]. On the other hand, recent study that compared serum BTP with serum cystatin C in elderly patients showed better correlation of cystatin C based estimated glomerular filtration rate with measured filtration rate [38].…”
Section: Discussionmentioning
confidence: 99%